To problems with continual derivative in boundary conditions for a parabolic equation - Kerefov, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We reduce problems with continual derivatives in boundary conditions for a parabolic equation to a system of two singular integral Volterra equations of the second order.